74.5k views
2 votes
Solve for x.
-3(2x – 1) – 3x – 4 = 17

User Nikolay R
by
3.9k points

2 Answers

4 votes

The Answer Is x=-2

Hope This Help's

User Jamesaharvey
by
4.9k points
4 votes

Answer:


\star \: \: \: \star \: \: \: \star \: \: \: \star \: \: \: \star \: \: \: \star \: \: \: \star \: \: \: \star \: \: \: \star \: \: \: \star \: \: \: \star \: \: \: \star

Explanation:


: \implies{ - 3(2x - 1) - 3x - 4 = 17}


: \implies{ - 6x + 3 - 3x - 4 = 17}


: \implies{ - 6x - 3x + 3 - 4 = 17}


: \implies{ - 9x - 1 = 17}


: \implies{ - 9x = 17 + 1}


: \implies{ - 9x = 18}


: \implies{ \displaystyle{x = (18)/( - 9) }}


\: \: \: \: \: \: \: \: \star{ \: \implies{ \red{x = - 2}}}

User Mez
by
4.9k points